John Mbiti: An African theologian fifty years and beyond - Kelebogile T. Resane (Verbum et Ecclesia, 2025)
This article provides an overview of John Mbiti and his African theology over the past half a century. It discusses how African theology has moved from being unwritten to more deliberate, organised, and written forms of articulation since the 1950s. It also discusses the life, teachings, writings and convictions of John S. Mbiti known as the ‘Father of African Theology’ who passed away in 2019. Mbiti’s contribution to African theological epistemologies is plausible and has for ages reasserted itself within the mainstream theological studies. Mbiti put African spirituality worldview into perspective and made it a discipline acceptable by both African and international academics. Key concerns of African theology include inculturation of the gospel into the African context, liberation from forces hindering Africans, communicating Christ’s message in an African manner, and asserting African self-identity and universality of the gospel. The article outlines some of the major themes of Mbiti’s African theology since the mid-20th century. It hopes to sketch an emerging agenda for African Christian theologies in the 21st century. This emerging agenda is African theology beyond Mbiti, which is a call to current African scholars from all the academic disciplines to take Mbiti’s convictions further by expanding them into the broader epistemologies.